2006
DOI: 10.1063/1.2206136
|View full text |Cite
|
Sign up to set email alerts
|

In situ x-ray diffraction study of the thermal expansion of the ordered arrays of silver nanowires embedded in anodic alumina membranes

Abstract: Thermal expansion of as-prepared and annealed ordered arrays of silver nanowires embedded in anodic alumina membranes (AAMs) was studied by in situ x-ray diffraction measurement in the temperature range from 25to800°C. The axial thermal expansion coefficient (TEC) for the as-prepared nanowires is 6.35×10−9∕°C and 6.02×10−6∕°C below and above 650°C, respectively. However, the TEC of the annealed sample turns from 2.32×10−6∕°Cto12.06×10−6∕°C when the temperature is above 350°C. The collective effects of the intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
25
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 16 publications
1
25
0
Order By: Relevance
“…The thermal expansion coefficient of Ni nanocrystallites in the polycrystalline Ni nanowires was estimated to be 1.7 × 10 -5 K -1 as in the bulk Ni, enabling to conclude that there is, as well as in bulk Ni, enough space between nanocrystallites to release the stress from the lattice expansion during heat treatment. The thermal expansion of single crystalline Ag nanowires with the axis direction along the [220] crystallographic direction deposited within the alumina pores (Ø pore ∼55 nm) was studied by determining the axial lattice parameter and the state of vacancies in nanowires for the first and repeated annealing in vacuum (Xu et al 2006). In this study it was shown that the plots of variation of axial lattice parameter for as-grown and annealed silver nanowires can be divided into two regions.…”
Section: Annealing Effects In Nanowiresmentioning
confidence: 99%
“…The thermal expansion coefficient of Ni nanocrystallites in the polycrystalline Ni nanowires was estimated to be 1.7 × 10 -5 K -1 as in the bulk Ni, enabling to conclude that there is, as well as in bulk Ni, enough space between nanocrystallites to release the stress from the lattice expansion during heat treatment. The thermal expansion of single crystalline Ag nanowires with the axis direction along the [220] crystallographic direction deposited within the alumina pores (Ø pore ∼55 nm) was studied by determining the axial lattice parameter and the state of vacancies in nanowires for the first and repeated annealing in vacuum (Xu et al 2006). In this study it was shown that the plots of variation of axial lattice parameter for as-grown and annealed silver nanowires can be divided into two regions.…”
Section: Annealing Effects In Nanowiresmentioning
confidence: 99%
“…Actually, the thermal expansion of the above‐mentioned nanoarchitectures in our experiments is mainly dependent on their nonlinear crystal‐lattice vibrations, which may include the vacancies and vacancy clusters moving to and escaping from the surface of the NT or NW, rearrangement of the Cu atoms, and extrusion induced by the limit effect of AAO‐template expansion with temperature increase 22, 25. It should be mentioned that the thermal expansion of the AAO template ( α = 7.7 × 10 −6 °C −1 )22 extrudes these nanoarchitectures and contributes to expansion along both the axial and lateral directions of the NTs or NWs.…”
mentioning
confidence: 94%
“…It can be seen that the lattice parameters of the stem (for Y‐shaped topology) and the large‐diameter segments (for step‐shaped topology) of copper NTs and NWs increase more quickly with temperature than those of their branch and small‐diameter counterparts, respectively. It should be noted that the samples can hardly be put in the same position in the XRD experiment chamber and thus the starting values of the axial lattice parameters for the counterparts of the nanostructures are not the same 22. In addition, it can be seen from Figure 4b–d that the lattice parameters of copper NTs are more sensitive to temperature than those of copper NWs of the same diameter.…”
mentioning
confidence: 98%
“…As one kind of 1D nanomaterials, metallic nanostructures are expected to be used as active components or interconnects in the fabrication of nanoscale devices, such as in magnetic, electronic, and optoelectronic devices. [1][2][3][4][5][6][7][8] As 1D nanostructures, ferromagnetic nanostructures have attracted considerable interests due to their applications for variety of new materials and devices such as data-storage media, spin electronics and memory device. 9 Fe nanostructures are the important ferromagnetic material, and the researches on Fe nanowires are commonly related to the properties of magneto-optical 10 and magnetic propreties.…”
mentioning
confidence: 99%